Intrapartum fetal abdominal circumference by ultrasonography for predicting fetal macrosomia. - Ratchanikon Loetworawanit (2018)
OBJECTIVE: To evaluate the diagnostic value of sonographic measurement of fetal abdominal circumference (AC) for the prediction of fetal macrosomia. MATERIAL AND METHOD: A prospective clinical trial was conducted at Department of Obstetrics and Gynecology, Ramathibodi Hospital, Mahidol University, Bangkok, Thailand. The study consisted of 361 singleton pregnant women who were admitted for delivery at labor room. All women underwent sonographic measurements of the fetal abdominal circumference (AC) during the early intrapartum period. The AC values were correlated to actual fetal birth weight. The cut-off value of AC for predicting of fetal macrosomia was analyzed. RESULTS: Among 361 cases, the mean maternal age was 29.0 +/- 5.5 years (range, 15-46). The median gestational age was 39 weeks (range, 31-42). The mean fetal birth weight was 3,179.83 +/- 450.91 gm (range, 1,180-4,560). The prevalence of macrosomia was 11.08% (40/361). A cut-off value of abdominal circumference > or = 35 cm was the best predicting of fetal macrosomia. The sensitivity, specificity, accuracy, positive predictive value, and negative predictive value were 87.50%, 84.74%, 85.04%, 41.67%, and 98.19%, respectively. CONCLUSION: The intrapartum fetal AC measurement was useful in predicting of fetal macrosomia. An AC measurement of > or = 35 cm was the best value of fetal macrosomia prediction.